Endoglucanase Production By Bacillus Amyloliquefaciens Using Coffeepulp As Substrate In Solid State Fermentation - THANGASWAMY SELVANKUMAR; MUTHUSAMY GOVARTHANAN; MUNISAMY GOVINDARAJU (International Journal of Pharma and Bio Sciences, 2011)
In this study, endoglucanase was produced from coffee pulp waste by Bacillus amyloliquefaciens MTCC610. The effects of the fermentation parameters such as pH, temperature, and the carbon source sucrose with different percentages (2% -10%) were used in coffee pulp substrate. The endoglucanase production was assayed using carboxymethyl cellulose (CMC) as the carbon source. B. amyloliquefaciens MTCC610 was maximally produced endoglucanase at 45°C, at pH 7.0 with 6% of sucrose as carbon source in addition with coffee pulp waste. The enzyme activity recorded during the fermentation was 780 U/ml after 72 hours of incubation. The productivity of the enzyme increased the substrate with sucrose (6%) in the fermentation medium. The 60 to 80 % of ammonium salt purification was improved upto 5.4 fold than the crude enzyme and further improved upto 9.0 fold by DEAE column chromatography. From this findings coffee pulp waste is an abundant solid waste at coffee processing industries, it has the potential substrate for endoglucanase production.